2012
DOI: 10.1186/1687-1499-2012-145
|View full text |Cite
|
Sign up to set email alerts
|

Unified approach to cross-layer scheduling and resource allocation in OFDMA wireless networks

Abstract: Orthogonal frequency division multiple access (OFDMA) has been selected as the core physical layer access scheme for state-of-the-art and next-generation wireless communications standards. In these systems, scheduling and resource allocation algorithms, jointly assigning transmission data rates, bandwidth and power, become crucial to optimize the resource utilization while providing support to multimedia applications with heterogeneous quality of service (QoS) requirements. In this article, a unified framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…As summarized in [20], the weights w k can be chosen based on different optimization criteria resulting in a wide class of scheduling algorithms (e.g., the max-sum rate (MSR), the proportional fair (PF), the modified largest weighted delay first (M-LWDF), or the exponential (EXP)). Building on the semiorthogonal user selection (SUS) algorithm proposed by Yoo and Goldsmith in [3], the GMSUS algorithm can be summarized as follows:…”
Section: A Virtual Users Selection Scheduling Algorithmsmentioning
confidence: 99%
“…As summarized in [20], the weights w k can be chosen based on different optimization criteria resulting in a wide class of scheduling algorithms (e.g., the max-sum rate (MSR), the proportional fair (PF), the modified largest weighted delay first (M-LWDF), or the exponential (EXP)). Building on the semiorthogonal user selection (SUS) algorithm proposed by Yoo and Goldsmith in [3], the GMSUS algorithm can be summarized as follows:…”
Section: A Virtual Users Selection Scheduling Algorithmsmentioning
confidence: 99%
“…: R → R, p ∈ R |K h | , and U is the number of constraints. By mapping (26) to (16), it can be observed that S = P max,h and U = 1. To prove that the duality gap is zero, we first provide the definition of the time-sharing condition as follows.…”
Section: Appendix E Proof Of Theoremmentioning
confidence: 98%
“…This weight setting allows for achieving a good balance between spectral efficiency, QoS provisioning and fairness for GBR flows [21]. For nonGBR flows, we follow the proportional fairness (PF) rule [26] by setting w c (t) = 1 R (t) to attain a good tradeoff between spectral efficiency and fairness for the nonGBR flows [21].…”
Section: B Packet Scheduling and Power Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing allocation algorithms include water-filling algorithm [10], transmit power adaptation method [11], and linear programming relaxation method of integer programming [12]. Femenias et al presented a unified framework for quality of service guaranteed cross-layer scheduling and resource allocation in orthogonal frequency division multiple access (OFDMA) wireless networks [13]; a new quasioptimal algorithm was proposed to handle allocation problem and simulation results demonstrated the goodness of the framework. Chen et al studied adaptive resource allocation in downlink OFDM wireless systems by using a three-round subcarrier assignment step [14].…”
Section: Problem Overview and Related Workmentioning
confidence: 99%